The Justification of Criminal Law in Jakobs and its Consequences for the Exercise of Jurisdictional Power in a Constitutional State - Montoya Vivanco, Yván (2006)
This paper examines the political and criminal implications of Jakobs' recent conception of the Peruvian judicial system within a state where the Constitution is the supreme rule. The analysis highlights the shortcomings of Jakobs' thesis of positive general prevention in relation to the function of criminal law in our legal system. The article argues that Jakobs' approach disregards important constitutional principles and fails to consider fundamental rights that protect individuals from excessive use of punitive power by the State. This can lead to a dangerous weakening of the role of the courts. Consequently, this would undermine the functions of judicial operators and increase the power of the criminal legislator, which is not in line with the principles of a democratic state.